Role of the Mmr Efflux Pump in Drug Resistance in Mycobacterium tuberculosis - Rodrigues, Liliana (American Society for Microbiology, 2013)
Efflux pumps are membrane proteins capable of actively transporting a broad range of substrates from the cytoplasm to the exterior of the cell. Increased efflux activity in response to drug treatment may be the first step in the development of bacterial drug resistance. Previous studies showed that the efflux pump Mmr was significantly overexpressed in strains exposed to isoniazid. In the work to be described, we constructed mutants lacking or overexpressing Mmr in order to clarify the role of this efflux pump in the development of resistance to isoniazid and other drugs in M. tuberculosis. The mmr knockout mutant showed an increased susceptibility to ethidium bromide, tetraphenylphosphonium, and cetyltrimethylammonium bromide (CTAB). Overexpression of mmr caused a decreased susceptibility to ethidium bromide, acriflavine, and safranin O that was obliterated in the presence of the efflux inhibitors verapamil and carbonyl cyanide m-chlorophenylhydrazone. Isoniazid susceptibility was not affected by the absence or overexpression of mmr. The fluorometric method allowed the detection of a decreased efflux of ethidium bromide in the knockout mutant, whereas the overexpressed strain showed increased efflux of this dye. This increased efflux activity was inhibited in the presence of efflux inhibitors. Under our experimental conditions, we have found that efflux pump Mmr is mainly involved in the susceptibility to quaternary compounds such as ethidium bromide and disinfectants such as CTAB. The contribution of this efflux pump to isoniazid resistance in Mycobacterium tuberculosis still needs to be further elucidated.